Co-designing a civics curriculum: young people, democratic deficit and political renewal in the EU. Issue 2 (3rd March 2016) - Bessant, Judith; Farthing, Rys; Watts, Rob
Abstract : Contemporary discussion of the 'crisis in democracy' displays a tendency to see young people as the problem because they are 'apolitical', 'apathetic' and 'disengaged', or point to deficiencies in institutions deemed responsible for civic education. This discussion normally comes as a prelude to calls for more civics education. This article points to a renewal of politics at the hands of young people relying on new media, and draws on evidence like survey research, case studies and action research projects. This political renewal is occurring largely in response to the assumption of political elites that a 'politics-as-usual' will suffice to address the major political challenges of our time. Against the assumption that teachers, curriculum experts and policy-makers already know what kinds of knowledge and skills students need to become good citizens, we make a case for co-designing a contemporary citizenship curriculum with young people to be used for the professional development of policy-makers. We argue that such an intervention is likely to have a salutary educational effect on policy-makers, influence how they see young people's political engagement and how they set policy agendas. The article also canvasses the protocols such a project might observe.